2023
DOI: 10.1093/mnras/stad098
|View full text |Cite
|
Sign up to set email alerts
|

Improving Star Cluster Age Estimates in PHANGS-HST Galaxies and the Impact on Cluster Demographics in NGC 628

Abstract: A long-standing problem when deriving the physical properties of stellar populations is the degeneracy between age, reddening, and metallicity. When a single metallicity is used for all star clusters in a galaxy, this degeneracy can result in ”catastrophic” errors for old globular clusters. Typically, approximately 10 – 20 % of all clusters detected in spiral galaxies can have ages that are incorrect by a factor of ten or more. In this paper we present a pilot study for four galaxies (NGC 628, NGC 1433, NGC 13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 88 publications
0
16
0
Order By: Relevance
“…For example, a maximum E(B − V ) of 1.5 mag was adopted by the LEGUS (Calzetti et al 2015) and PHANGS (e.g., Turner et al 2021;Lee et al 2022) cluster surveys, and by Adamo et al (2010Adamo et al ( , 2011a for the clusters in ESO 185-IG13, ESO 338-IG04, and Haro 11. However, adopting a single, large value like 1.5 mag for the maximum E(B − V ) can result in serious problems in the estimated ages for clusters older than ≈10 Myr, as explored and discussed in detail by Whitmore et al (2020Whitmore et al ( , 2023.…”
Section: Methods and Checksmentioning
confidence: 99%
See 3 more Smart Citations
“…For example, a maximum E(B − V ) of 1.5 mag was adopted by the LEGUS (Calzetti et al 2015) and PHANGS (e.g., Turner et al 2021;Lee et al 2022) cluster surveys, and by Adamo et al (2010Adamo et al ( , 2011a for the clusters in ESO 185-IG13, ESO 338-IG04, and Haro 11. However, adopting a single, large value like 1.5 mag for the maximum E(B − V ) can result in serious problems in the estimated ages for clusters older than ≈10 Myr, as explored and discussed in detail by Whitmore et al (2020Whitmore et al ( , 2023.…”
Section: Methods and Checksmentioning
confidence: 99%
“…We believe there are two main reasons for the differences described above: (1) we include Hα photometry directly in the SED fits, and (2) Adamo et al (2010, 2011a) adopted a significantly higher maximum E(B − V ) of 1.5 mag in their age-dating procedure, compared with the 0.1 mag we adopt for nearly all clusters. SED fits that only include broadband colors struggle to break the age-reddening degeneracy and can result in a number of systematic, 'catastrophic' failures in age-dating, with many older clusters with little reddening erroneously fit by a combination of young age and high reddening (e.g., Whitmore et al 2020Whitmore et al , 2023M. Floyd et al, in preparation).…”
Section: Comparison With Previous Workmentioning
confidence: 99%
See 2 more Smart Citations
“…While the PHANGS-HST study estimates ages correctly for many clusters, incorrect determinations have been found to disproportionately affect the ancient GC populations. Whitmore et al (2023) andM. Floyd et al (2023, in preparation) have found that ∼80% of ancient GCs, which comprise ≈5%-10% of the PHANGS cluster catalogs, have been incorrectly age-dated, with both too young ages and too high reddening.…”
Section: Agementioning
confidence: 99%